2023
DOI: 10.1002/jcaf.22644
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of business ethics and diversity on ESG disclosure: Evidence from Hong Kong

Abstract: This paper investigates the effects of board cultural diversity, audit committee experience diversity as well as business ethics on the effectiveness of oversight quality on ESG performance. Using Generalized Moments of Methods (GMM), we examine the ESG performance of the firms listed in the Hong Kong Hang Seng Composite Index between 2010 and 2015. We find that board cultural diversity and business ethics have positive correlations with ESG performance while audit committee experience diversity has a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Additionally, the literature has examined the impact of corporate governance sustainability issues on ESG performance [74][75][76][77][78][79][80], such as the positive impact of gender diversity and the percentage of women on ESG performance [79,81]. A recent literature review of 49 articles found a positive impact of integrating ESG criteria with corporate sustainability performance, such as improving firm image, competitiveness, and intellectual opportunities [82].…”
Section: Literature Review 21 Environmental Social and Governance (Esg)mentioning
confidence: 99%
“…Additionally, the literature has examined the impact of corporate governance sustainability issues on ESG performance [74][75][76][77][78][79][80], such as the positive impact of gender diversity and the percentage of women on ESG performance [79,81]. A recent literature review of 49 articles found a positive impact of integrating ESG criteria with corporate sustainability performance, such as improving firm image, competitiveness, and intellectual opportunities [82].…”
Section: Literature Review 21 Environmental Social and Governance (Esg)mentioning
confidence: 99%